Optical properties of graphene oxide - Tene, Talia; Guevara, Marco; Benalcázar Palacios, Freddy; Morocho Barrionuevo, Tania Paulina; Vacacela Gomez, Cristian; Bellucci, Stefano (Frontiers in Chemistry, 2023)
The study of the optical properties of graphene oxide (GO) is crucial in designing functionalized GO materials with specific optical properties for various applications such as (bio)sensors, optoelectronics, and energy storage. The present work aims to investigate the electronic transitions, optical bandgap, and absorption coefficient of GO under different conditions. Specifically, the study examines the 2 This is a provisional file, not the final typeset article effects of drying times ranging from 0 to 120 h while maintaining a fixed temperature of 80°C and low temperatures ranging from 40 ℃ to 100 ℃, with a constant drying time of 24 h. Our findings indicate that exposing the GO sample to a drying time of up to 120 h at 80°C can lead to a reduction in the optical bandgap, decreasing it from 4.09 eV to 2.76 eV. The 𝜋 − 𝜋 * transition was found to be the most affected, shifting from approximately 230 nm at 0 h to 244 nm after 120 h of drying time. Absorption coefficients of 3140 to 5507 ml mg -1 m -1 were measured, which are similar to those reported for exfoliated graphene dispersions but up to two times higher, confirming the improved optical properties of GO. Our findings can provide insights into determining the optimal temperature and duration required for transforming GO into its reduced form for a specific application through extrapolation.The study is complemented by analyzing the elemental composition, surface morphology change, and electrical properties.